2010
DOI: 10.1136/bjo.2010.188003
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of supplemental intracameral lidocaine during phacoemulsification under topical anaesthesia: a randomised controlled trial

Abstract: The use of 0.5 cc of 1% intracameral lidocaine during phacoemulsification under topical anaesthesia significantly reduces pain experienced by patients. Risk factors for pain include females, non-Chinese and previous cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 35 publications
6
30
0
2
Order By: Relevance
“…Similarly, Apil et al 6 reported that intraoperative pain was not associated with age or gender in their study. However, in a study including 506 patients, Tan et al 18 found that female patients experienced more pain during cataract surgery, while Gombos et al 19 reported that young patients were more sensitive to pain during cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Apil et al 6 reported that intraoperative pain was not associated with age or gender in their study. However, in a study including 506 patients, Tan et al 18 found that female patients experienced more pain during cataract surgery, while Gombos et al 19 reported that young patients were more sensitive to pain during cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that the use of supplementary intracameral lidocaine injection with topical anesthesia is an effective and safe adjunct for decreasing intraoperative pain [18, 19], whereas another study reported there was no significant difference when using additional intracameral anesthesia [20]. This procedure might be necessary according to the needs of the surgeon or patient.…”
Section: Discussionmentioning
confidence: 99%
“…The use of lidocaine gel as a topical anes thetic in phacoemulsification is thought to hydrate the cornea thus improving visualization by the surgeon during surgery and to reduce the need for the postoperative administration of a balanced salt solution (BSS) (19) . Intracameral addition of lidocaine is performed quite often (20)(21)(22)(23)(24) ; because in topical approaches only the trigeminal nerve ends in the cornea and conjunctiva are anesthetized, whereby complementary anesthesia by means of intracameral unpreserved lidocaine is nee- ded to avoid the irritation of the ciliary nerves due to occasional manipulation of the iris. Current evidence shows that intracameral lidocaine as a supplement in topical anesthesia induces significant reduction in pain perception during surgery when compared with topical anesthesia alone.…”
Section: Discussionmentioning
confidence: 99%